Pengaruh Media Booklet Terhadap Peningkatan Pengetahuan Dan Sikap Ibu Dalam Mendeteksi Perkembangan Balita Usia 24-36 Bulan - Wahyu Ersila; Lia Dwi Prafitri; Rifqi Sabita (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: At the age of 0-60 months is a period of growth and development that is considered the most extraordinary and amazing. This age is referred to as the golden age. The development of the child's brain structure is very sensitive to the stimulus or stimulus provided. If stimulation is done optimally within a certain time span, then development will occur as it should, but when stimulation is given less precisely or there are disturbances from the environment, there will be obstacles in development in children. This study aims to analyze the influence of box media on the knowledge and attitude of mothers regarding the detection of the development of toddlers aged 24-36 months.Methods:  This research method uses quasi experiments with the design of pre post desaign without control group. The sample in this study is posyandu mother in the village of tangkil kedungwuni subdistrict with sampling technique is cluster random sampling. The tool used is a questionnaire with the questionnaire method. Bivariate data analysis uses the Wilcoxon test for knowledge variables and paired t test for attitude variables.Results:  The result is good category knowledge before 46.7% and good category knowledge after increasing to 83.3%; Good attitude before 50% good attitude after increasing to 56.7%. While the influence of booklets on knowledge there is an influence on the increase in knowledge p <0.001, attitude value p <0.001 which means there is an influence of booklet on knowledge and attitude before and after the provision of media booklet.Conclusion:  Booklet can be used as one of the alternative media in providing health education so as to improve the knowledge and attitude of the mother in developing detection for her child.